Trichoscopic features in female pattern hair loss: 1-Year hospital-based cross-sectional study - Chintan Ramesh Kothari; Shivakumar Patil (Wolters Kluwer Medknow Publications, 2024)
Introduction: Female pattern hair loss (FPHL) a nonscarring alopecia, is a common cause of hair loss in women. FPHL shows miniaturization of the hair follicles with thinning of hair. Scalp biopsy is diagnostic of FPHL but usually not needed. Trichoscopy a noninvasive higher magnification method (vs. scalp biopsy) for diagnosis of hair loss allows measurement of anisotrichosis characteristic of FPHL. Materials and methods: A total of 110 patients with clinically diagnosed FPHL of all grades were subjected to clinical and trichoscopic examination, and findings were looked for and compared with the occipital region serving as control. Results: Trichoscopic features apart from yellow dots and 2-3 hairs per unit follicle (HU) were statistically significant like hair diameter diversity, brown and white peripilar sign, one hair per follicular unit, white dots (WD), fine scaling, and honey-comb pigmentation (HCP). Focal atrichia, 2-3 hairs/HU, WD, HCP correlated with the grade of hair loss. Conclusion: Trichoscopy could be excellent tool for diagnosing FPHL in early stages and may aid in differentiating it from other conditions like chronic telogen effluvium and obviating the need of painful procedures like scalp biopsy. The study lacks histo-pathological and hormonal investigations however past studies done have already established correlation of trichoscopic and histo-pathological changes.